2012
DOI: 10.1038/ng.2270
|View full text |Cite
|
Sign up to set email alerts
|

Detectable clonal mosaicism and its relationship to aging and cancer

Abstract: In an analysis of 31,717 cancer cases and 26,136 cancer-free controls drawn from 13 genome-wide association studies (GWAS), we observed large chromosomal abnormalities in a subset of clones from DNA obtained from blood or buccal samples. Mosaic chromosomal abnormalities, either aneuploidy or copy-neutral loss of heterozygosity, of size >2 Mb were observed in autosomes of 517 individuals (0.89%) with abnormal cell proportions between 7% and 95%. In cancer-free individuals, the frequency increased with age; 0.23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
498
4
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 536 publications
(551 citation statements)
references
References 43 publications
40
498
4
3
Order By: Relevance
“…41,43,44 A substantial proportion of patients with persistent cytopenia lack conclusive morphology and cytogenetics and may presumptively be classified as ICUS. 45,46 The difficulty in diagnosing MDS among AA patients lies in the fact that both conditions often show indistinguishable phenotypes and may even coexist in the same patients, although patients with AA are nevertheless at high risk for MDS development.…”
Section: Diagnosing Mds In Aa Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…41,43,44 A substantial proportion of patients with persistent cytopenia lack conclusive morphology and cytogenetics and may presumptively be classified as ICUS. 45,46 The difficulty in diagnosing MDS among AA patients lies in the fact that both conditions often show indistinguishable phenotypes and may even coexist in the same patients, although patients with AA are nevertheless at high risk for MDS development.…”
Section: Diagnosing Mds In Aa Patientsmentioning
confidence: 99%
“…It was originally suggested by the studies on NRXI 53,54 and has recently been investigated more extensively using advanced genomics. By reanalyzing SNP array data generated for .50 000 individuals who did not carry hematologic cancer, Jacobs et al 43 and Laurie et al 44 demonstrated that CNAs and UPDs were observed at increasing frequencies in peripheral blood from elderly people (;2% to 3%) compared with those from younger people (;,0.5%) (ARCH). Some authors describe the same phenomenon under the term "CHIP" (CH with indeterminate potential), although the potential may not be totally indeterminate.…”
Section: Age-related Ch In the General Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of intensity data tracks from single nucleotide polymorphism (SNP) array analysis of peripheral blood DNA from older individuals (typically >60 years) in population cohorts has revealed large somatically-acquired chromosomal duplications, deletions and regions of acquired uniparental disomy (aUPD; also known as copy number neutral loss of heterozygosity) similar to those seen in individuals with a hematological malignancy [1][2][3][4] . Such variants are typically present in a proportion of peripheral blood cells at a specific time-point but their frequency can increase or decrease over time and even disappear, suggesting a dynamic pattern of clonal change 1 .…”
Section: Detection Of Leukemia-associated Mutations In Peripheral Blomentioning
confidence: 99%
“…In recent years, many groups have performed high-resolution screening of somatic cell populations 1,6,11,12 as well as hiPSC and hESC 7,8 and have reported de novo CNVs ranging from 10 kb to several Mb. It is important to bear in mind that these studies are based on the analysis of DNA from extractions from large numbers of cells, which only allows detection of CNVs if they are present in at least 5-10% of the cells 11,12 .…”
mentioning
confidence: 99%